The experiences of medical students, residents, fellows, and attendings in the emergency department: Implicit bias to microaggressions. (29th September 2021) - Brown, Cortlyn; Daniel, Rosny; Addo, Newton; Knight, Starr
Abstract: Objectives: Microaggressions and implicit bias occur frequently in medicine. No previous study, however, has examined the implicit bias and microaggressions that emergency medicine (EM) providers experience. Our primary objective was to understand how often EM providers experience implicit bias and microaggressions. Our secondary objective was to evaluate the types of microaggressions they experience and whether their own identifying characteristics are risk factors. Methods: A questionnaire was administered to EM providers across the United States. Outcome measures of experiencing or witnessing a microaggression, overt discrimination, or implicit bias were described using frequencies, proportions, and logistic regressions. Where a univariate association between outcome measures and demographic characteristics was found, multivariate regression to estimate odds ratios (ORs) and 95% confidence intervals (95% CIs) was performed. Proportional odds logistic regression models were used to evaluate the specific type of microaggressions experienced and if there was an association with demographic variables. Results: A total of 277 medical providers (48% trainees—medical students, residents, and fellows—and 52% attending physicians) completed the survey. A total of 181 (65%) respondents reported experiencing a microaggression. Female (OR = 5.9 [95% CI = 3.1 to 11.2]) and non‐White respondents (OR = 2.4 [95% CI = 1.2 to 4.5]) were more likely to report experiencing any microaggression. Misidentification, the most common form of microaggression, was more common with trainees compared to attending physicians (proportional OR [POR] = 2.6 [95% CI = 1.7 to 4.0]) and non‐White, compared to White, respondents (POR = 2.2 [95% CI = 1.3 to 3.6]). Misidentification as nonclinician staff was associated with gender (POR = 53 [95% CI = 24 to 116]) and 52% of female respondents reported being mistaken for nonclinician staff almost daily. Seventy‐six percent of respondents reported being called a vulgar term by a patient and 21% by a staff member. Conclusions: EM providers, particularly women and non‐Whites, who responded to our survey experienced and witnessed bias and microaggressions, most commonly misidentification, in the ED.